Estimating the Effects of Potential Benefit Duration without Variation in the Maximum Duration of Unemployment Benefits - Tomi Kyyrä; Hanna Pesola (Institute of Labor Economics (IZA), 2017)
This paper examines the effects of unemployment benefit duration in Finland. To overcome the problem that the maximum duration of benefits is the same for all unemployed we exploit two observations. First, despite the uniform maximum benefit period, potential benefit duration at the beginning of unemployment spells varies across individuals because only those with sufficient work history in the past two years qualify for a new period of benefits whereas others may be entitled to unused benefit days from a previous spell. Second, part of this variation is exogenous due to a reform that reduced the minimum number of employment weeks required for the new benefit period. Using the exogenous part of the variation for identification we estimate that one extra week of benefits increases expected unemployment duration by 0.15 weeks, which corresponds to an elasticity of 0.5. We also find positive effects on the quality of the next job, especially when measured by job stability.
Keywords: J64; J65; 330; eligibility conditions; unemployment duration; unemployment insurance